The Impact of Policy Orientation on Green Innovative Performance: The Role of Green Innovative Capacity and Absorptive Capacity - Li, Bin; Lei, Yongxin; Hu, Minqi; Li, Wenjing (Frontiers in Environmental Science, 2022)
Green innovation has been recognized as a key factor for balancing environmental sustainability and financial growth. Although the literature has examined the impacts of policy orientation on green innovation, there are still outstanding issues to be addressed. On the one hand, existing studies have focused on the direct impact of environmental regulation or institutional pressure on green innovation, but fail to account for the issue of intermediate mechanisms between policy orientation and green innovations. On the other hand, there are inconsistent findings in the current empirical evidence on the impact of environmental policies on green innovation. Therefore, this study tries to address these research gaps by clarifying the internal mechanisms and boundary conditions between policy orientation and green innovation. Based on Porter’s hypothesis and absorptive capacity perspective, this study explores the mediation effect of green innovative capability and the moderation effect of absorptive capacity in the relationship between policy orientation and green innovative capacity. To test the research model, we collected data from 359 Chinese green manufacturing companies. Our findings suggest that whether policy orientation has a significant positive effect on a firm’s green innovation performance depends on the firm’s absorptive capacity. In addition, green innovative capacity mediated the effect of policy orientation on green innovation performance. Furthermore, absorptive capacity strengthens this mediation effect. Therefore, we identified the mediating role of green innovative capacity and the moderating role of absorptive capacity between policy orientation and green innovation performance. Our findings theoretically enrich the literature on Porter’s hypothesis and absorptive capacity perspectives and provide a reference for green innovation practices.